2011
DOI: 10.1111/j.1346-8138.2011.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic detection of nail fold capillary abnormality in patients with systemic sclerosis

Abstract: The diagnosis of systemic sclerosis (SSc) is often difficult. The purpose of the present study was to find the distribution of nail fold capillary abnormality in SSc. Sixty-two patients with SSc (male : female = 7:55, age 21-86 years, mean 60.1) admitted to the outpatient clinics were studied. Eighteen age- and sex-matched normal subjects, 28 patients with systemic lupus erythematosus (SLE) and 10 with dermatomyositis (DM) were also studied. Nail fold capillary loops were observed under immersion oil at a magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…24 Ohtsuka evaluated 62 patients of SSc with dermoscope and found higher incidence of dilated capillaries (43.5%), avascular areas (25.8%), and nailfold bleeding (12.9%). 25 Similar patterns may be found in patients with other connective tissue diseases (eg., dermatomyositis, SLE, and MTCD). In primary Raynaud's phenomenon, capillaroscopy is normal, however, those associated with connective tissue disease show capillaroscopic alterations.…”
Section: Ijdysupporting
confidence: 63%
“…24 Ohtsuka evaluated 62 patients of SSc with dermoscope and found higher incidence of dilated capillaries (43.5%), avascular areas (25.8%), and nailfold bleeding (12.9%). 25 Similar patterns may be found in patients with other connective tissue diseases (eg., dermatomyositis, SLE, and MTCD). In primary Raynaud's phenomenon, capillaroscopy is normal, however, those associated with connective tissue disease show capillaroscopic alterations.…”
Section: Ijdysupporting
confidence: 63%
“…To the best of our knowledge, this is the first study to compare NFC abnormalities among CTDs and the normal population with this method. Although information regarding the comparison of NFC features in patients with autoimmune CTDs vs. healthy controls has been previously reported in Caucasian and Japanese individuals (44,45), there is no data in the Southeast Asian population. We confirm that numerous onychoscopic microvascular parameters in the morphologic indexes (i.e., bushy capillaries, elongated capillaries, subpapillary plexus, and hemorrhage), diameter patterns (i.e., enlarged capillaries), architectural forms (i.e., disorganized and avascular pattern), and decreased capillary density were distinct features for CTDs and rarely seen in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…13 Some studies showed dilated capillaries, nail-fold bleeding, and avascular areas to be common in patients with SLE. 14 The incidence of microhemorrhages was significantly higher in patients with active SLE disease, triggered by vasospasm, vasculitis, or thromboembolism. 15 Tunc et al reported subungual hemorrhaging was found in the fingernails of 11 of 28 (39.3%) patients with active SLE.…”
Section: Discussionmentioning
confidence: 91%